Poster Presentations 2019
DOI: 10.1136/annrheumdis-2019-eular.5646
|View full text |Cite
|
Sign up to set email alerts
|

FRI0237 OMEGA-3 AND OMEGA-6 FATTY ACIDS IN SJöGREN’S SYNDROME: CLINICAL IMPLICATIONS AND THEIR ASSOCIATION WITH INFLAMMATION

Abstract: Background:Essential ω-3 and ω-6 fatty acids (FA) are natural modulators of inflammation activity; however, their role in primary Sjögren’s syndrome (pSS) is unknown.Objectives:To evaluate the intake and serum levels of ω-3 and ω-6 FA in patients with pSS, and to correlate them with ocular and oral signs and symptoms, disease activity as well as with the presence of a panel of inflammatory chemokines/cytokines in saliva and tears.Methods:We included 108 patients with pSS according to EULAR/ACG criteria. We exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The first randomised trials evaluating the effectiveness of implementing omega-3 and omega-6 supplementation in supplementary treatment of this disease have been conducted in the last several years. It has been shown that supplementing omega-3 acids for 3 months leads to a statistically significantly increased amount of produced saliva (without stimulation) when compared to a placebo group [49], whilst the use of omega-3 acids in combination with omega-6 acids caused decreased activity of the disease evaluated with the ESSDAI index (EULAR Sjögren's syndrome disease activity index), as well as improvement of ocular lesions assessed with the Sicca Ocular Staining Score index, and it also increased the amount of produced saliva [50].…”
Section: Sjögren's Syndromementioning
confidence: 93%
“…The first randomised trials evaluating the effectiveness of implementing omega-3 and omega-6 supplementation in supplementary treatment of this disease have been conducted in the last several years. It has been shown that supplementing omega-3 acids for 3 months leads to a statistically significantly increased amount of produced saliva (without stimulation) when compared to a placebo group [49], whilst the use of omega-3 acids in combination with omega-6 acids caused decreased activity of the disease evaluated with the ESSDAI index (EULAR Sjögren's syndrome disease activity index), as well as improvement of ocular lesions assessed with the Sicca Ocular Staining Score index, and it also increased the amount of produced saliva [50].…”
Section: Sjögren's Syndromementioning
confidence: 93%